Hyperostosis Frontalis: A Review. Issue 2 (April 2018) - Murphy, Emily; Kortyna, Ricky; Flaherty, Donna
Abstract : Hyperostosis frontalis is the overgrowth of bone on the inner plate of the skull. The condition is most common in postmenopausal women, and it occurs in 5% to 12% of this population. A nutritional etiology has been given consideration because there has been an increased consumption of dietary phytoestrogens, as seen in soy, grain, and vegetables, compared with several centuries ago. Generally, because the extra bone growth seen with hyperostosis frontalis is asymptomatic or minimally symptomatic, there is no need to treat the bony overgrowth itself.